The first description of the larvae of the Chinese species Paraleuctra tianmushana Li & Yang (Plecoptera: Leuctridae) - Li, Weihai; Li, Kefan; Wang, Rongfeng; Yang, Ding (Zootaxa, 2016)
The pharate larval stage of Paraleuctra tianmushana Li & Yang is described for the first time. The yellowish-brown larvae of this species are characterized by a slender abdomen lacking setae and a unique pattern of dark pigmentation on the head, pronotum, and abdominal terga. Additionally, vestigial cervical gills in this species are present, a character not present in known Nearctic species.